Is the Welfare State Justified? - Shapiro, Daniel (Cambridge University Press, 2013)
This book came about, in a way, almost by accident. In the spring of 1995 I was looking for some external support during an upcoming sabbatical year to write some articles that the welfare state is not, by the standards used in mainstream political philosophy, just or fair, and I contacted Jeffrey Paul of the Social Philosophy and Policy Center at Bowling Green State University and asked him who might support such a project.